Heterogeneity of EGFR mutations in a patient treated with gefitinib as neo-adjuvant chemotherapy. (2015) - Mizoguchi, Kosuke; Nakamura, Yoichi; Abe, Kuniko; Takemoto, Shinnosuke; Motoshima, Kohei; Ogawara, Daiki; Nakatomi, Katsumi; Fukuda, Minoru; Fukuoka, Junya; Kohno, Shigeru
Abstract: Objective: Heterogeneity of EGFR mutations remains controversial. A case of completely resected lung adenocarcinoma after initial chemotherapy with gefitinib that showed intratumoral heterogeneity of EGFR mutations is reported. Patient and methods: A 68-year-old woman who presented with mild breathlessness was diagnosed with lung adenocarcinoma (cT3N1M0 stage IIIA) harboring the L858R point mutation. She received gefitinib as neo-adjuvant chemotherapy to reduce the tumor volume to avoid pneumonectomy, and she underwent right middle and lower lobectomies. The resected specimen showed two areas that were distinctly different pathologically and genetically within the tumor. One area consisted of viable cells, but the other consisted mostly of degenerated cells. Immunohistochemical staining and polymerase chain reaction-direct sequencing for each microdissected area were performed. Results: In the viable cells area, the L858R point mutation was detected by both methods, but it was not detected in the mostly degenerated cells area. Conclusion: These results suggest that there may be intratumoral heterogeneity of EGFR mutations, and the therapeutic effect of EGFR–TKIs could be limited only to mutant cells.